Teacher’s Strategies in Promoting The 21st Century Learning Skills on Online Class in Tourism Vocational High School - Rezandy, Made Aditya Pras; Artini, Luh Putu; Dewi, Ni Luh Putu Eka Sulistya (Jurnal Imiah Pendidikan dan Pembelajaran, 2020)
This study aimed to analyze the strategies of promoting 21st century learning skills used by English teachers on online class in tourism vocational high school. The strategies in promoting 21st century learning skills used by the English teachers were described using qualitative descriptive research design. The instruments used by teacher to collect the data were observation sheet to use for observing the strategies appeared during the online class activities; and interview guide to know the perspective of the English teacher about the supporting and the challenging factors in using the strategies. The findings showed that from 9 strategies, 7 of them are used by the teachers. The most used strategy is the first strategy: using relevant material and topic. On the other hand, the seventh strategy: Enhancing teamwork as the outcome is not used by all the subjects of this research. The reason which is told by most of the teachers is because of the difficulty they faced in conducting teamwork project during online class effectively due to the recent issue. From 9 strategies, using relevant material and exploiting technology into class activities are the most used by the teachers among others. And from Nine strategies provided, 8 strategies used by the English teachers. The only strategy which is not used is the seventh strategy: Teamwork as the outcome. The teachers stated that creating group work based activities through online is not easy.